Response of breeding and gestating sows to a dietary source of lactobacillus acidophilus - Koch, B.A.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
During the breeding period, adding the fermentation product (lactobacillus acidophilus) to the ration fed to gilts and sows made no difference in conception percentages. Nonsignificant differences was observed between the control group and the group receiving the additive in number of pigs born dead or alive and weight of pigs at 2 or 4 weeks of age.
Swine Industry Day 1971 is known as Swine Day, 1971
Keywords: Swine; Lactobacillus acidophilus; Breeding sows; Gestation